Density of thin films of cryovacuum condensates of methane - Drobyshev, A.S.; Sokolov, D.Yu.; Shinbayeva, A.K.; Nurmukan, A.Y.; Duisebayev, T.S. (Recent Contributions to Physics, 2017)
In this paper, the dependence of the density ρ of cryocondensates of methane CH4 from the condensation temperature T is studied. We propose to consider the results obtained directly during the cryocondensation of samples in a substantially nonequilibrium state. This work dedicated to attempt to clarify the nature of the non-equilibrium state. These values of the density ρ of methane CH4 with decreasing condensation temperature T undergoes rupture in the vicinity of the phase transition temperature associated with the freezing of degrees of freedom of a quarter of molecules. A slight decrease in the density of methane with decreasing condensation temperature associated with an increase in porosity of samples of solid methane with decreasing condensation temperature. The error in measuring the density ρ does not exceed 4-5% and is determined mainly by the error in measuring the residual pressure of gaseous methane in the calibration volume, and also by a random error. These results can be used in astrophysical research.